Sisters-in-law : an uncensored guide for women practicing law in the real world - Sherman, Lisa G. (Sphinx Pub., 2004)
A MUST READ ... Loaded with wisdom, candor, insight and laugh-out-loud humor, Sisters-in-Law sets the standard in the legal profession for aspiring and practicing female lawyers, as well as their male counterparts.-Robert Shapiro The Essential Accessory for the Savvy Lawyer A fabulously wicked, uncensored romp into the world of lady legal eagles of the 21st century. Sisters-in-Law takes you behind the scenes of the old boys club and lets you in on the secrets that can make you the Queen of the courtroom or at least the Diva in a dark suit. These Sisters teach you what your law school professors didn't-about the nuts and bolts of practicing law, finding a specialty that suits your talents and moving from one firm to another-while addressing the demands of being a single gal, facing motherhood and perhaps managing a family. This hilarious trek through the years following law school provides the new attorney, as well as any veteran, with valuable insights. This uncensored guide will keep you focused on your career-but not too much! FUNNY, INFORMATIVE AND UTTERLY IRREVERENT! Sisters-in-Law is complete with real-life office antics, acres of advice and honest reassurance [that] neophyte lawyers will find nowhere else. I wish this book was available when I started law practice! -Karen Koenig, Of Counsel, Paul, Hastings, Janofsky & Walker.